Kegiatan Bisnis Layanan Pemeliharaan Ternak : Studi Kasus di Unit Breeding Services Elders Limited Australia (Animal Breeding Services Business Activity : Study Case in Breeding Services Unit at Elders Limited Australia) - Dyah Maharani (Faculty of Animal Science, Universitas Gadjah Mada, 2009)
This paper describes the business activity of animal breeding services in livestock services company at Elders Limited Australia. Primary and secondary data in this paper were collected from Elders Limited Australia database and Elders staff interviewed. Data were analyzed in full descriptively. The study indicated that the business of breeding services can help the farmer especially breeder to improve the genetic performance of their cattle farm and help them to make the decision of breeding program. The product of Elders Breeding Services are semen sales, breed exact and next exact program (breeding program), Taylor Made Seedstock (embryo transfer program). The breeding services also help farmers to promote their product by using Elders Limited website. In Australia, the using breeding services are more effective and efficient than the farmers conducting their farm by their own program.(Key words: Business activity, Breeding services, Elders Limited)